Reconciliation road : a family odyssey - Marshall, John Douglas (University of Washington Press, 2000)
In his prize-winning memoir, Reconciliation Road, John Marshall recounts a road trip around America in search of the truth about his famous grandfather General S.L.A. (Slam) Marshall, author of Pork Chop Hill. In the process he comes to terms with his own past and that of others whose families were torn apart by the Vietnam War.